Progress towards development of a genetically modified strain of the Australia sheep blowfly Lucilia cuprina suitable for a sterile release program : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Molecular Genetics at Massey University, Palmerston North, New Zealand - Li, Xuelei (Massey University, 2002)
The sterile insect technique (SIT) is concerned with the mass-rearing and release of sterilized insects which mate with "wild-type" females in the field, producing no viable offspring. The aim of this study was to use genetic engineering methods to make a strain of the Australia sheep blowfly Lucilia cuprina which is suitable for an area-wide sterile-male release program. The main objectives were: development of an efficient germline transformation system for introducing a target gene into Lucilia and development of an inducible female killing system to produce a male only population. The piggyBac and Minos transposons were evaluated as transformation vectors for L. cuprina. Firstly, Drosophila melanogaster was used as a model system to determine if the frequency of both inter-plasmid transposition and germ-line transformation increases with the level of expression of the piggyBac transposase. Expression of the piggyBac transposase gene was controlled with either the α1-tubulin, hsp83 or hsp70 promoter, which have strong, intermediate and low constitutive activity respectively. The results show that the frequency of piggyBac-mediated germ-line transformation does increase with the level of expression of the transposase. In contrast, there does not appear to be a simple correlation between the level of expression the transposase and the frequency of transposition measured using an inter-plasmid transposition assay. This suggests that this widely used assay may not necessarily predict which is the best "helper" plasmid for germ-line transformation. Secondly, inter-plasmid transposition assays have shown that both piggyBac and Minos transposases are active in blowfly embryos. Thirdly, Drosophila eye color genes and the enhanced green fluorescent protein (EGFP) gene were tested as potential markers for identifying transgenic flies. The most promising marker based on transient expression appears to be EGFP driven by the Drosophila polyubiquitin gene promoter (pUb-EGFP). Fourthly, blowfly embryos were coinjected with the piggyBac helper driven by the D. melanogaster hsp70 promoter and the PUbnlsEGFP marker gene. Two transgenic L. cuprina lines were isolated and characterised by Southern DNA hybridisation analysis and inverse PCR. The transformation frequency was 1.4 to 1.9%. Of the two transformant lines obtained, one had a single copy of the transgene and the other most likely has four copies. This is the first report of germ line transformation of L. cuprina. A tetracycline regulated inducible expression system was adopted to develop a controllable female-killing genetic system based on the D. melanogaster msl2 gene. One component of the system is the tetracycline dependent transactivator (tTA) gene controlled by a constitutive promoter. The other (tetO-msl2) is the msl2 coding region controlled with a promoter bearing seven copies of the tetracycline operator (tetO) sequence. Female D. melanogaster carrying both a promoter-tTA and tetO-msl2 gene constructs would be predicted to die in the absence of tetracycline due to expression of msl2. In this study several promoter-tTA constructs were developed including WH-arm which uses the constitutive armadillo promoter. Drosophila carring both WH-arm and tetO-lacZ transgenes were shown by spectrophotometric and histochemical staining assays to express β-galactosidase but only if raised on media that lacked tetracycline. There was a significant decrease in viability of females carrying both WH-arm and tetO-msl2 gene constructs raised on media lacking tetracycline. However lethality was not 100%. Assembly of the MSL complex on female X chromosomes (due to expression of msl2) was confirmed by immuno staining of polytene chromosomes with anti-MSL3 antibody. Thus it appears that induction of 100% female lethality will require higher levels of msl2 expression than obtained with the WH-arm/tetO-msl2 system for controlling female viability in transgenic Lucilia.
Keywords: Lucilia cuprina; Molecular genetics; Biological control; Australian sheep blowfly; Fields of Research::270000 Biological Sciences::270800 Biotechnology::270805 Genetic engineering and enzyme technology